Hippo Regius - Bûna - Bône: ein Erinnerungsort im Spiegel der kolonialzeitlichen Augustinusrezeption - Ardeleanu, Stefan (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2020)
"Hippo Regius - Bûna - Bône. A place of memory in the mirror of the colonial reception of Augustine" - This article analyzes the complex forms of St. Augustine’s perception in colonial Hippo Regius/Bône from 1832 to 1962. It emphasizes the narrow interconnectedness between early archaeological fieldwork and enthusiastic search for "Augustinian monuments" at the site of Hippo. Three phases of St. Augustine’s functionalization as crucial figure of a developing lieu de mémoire at Hippo are made out. A special focus is placed on the monuments and the illustrious festivities dedicated to St. Augustine in Hippo and Bône. Several other contemporaneous sources (literature, travel reports, official stamps, post cards, films, press articles and excavation reports) complement to a barely known complex picture of the slow creation of a highly ideological place celebrating the ‘resurrected Church’ in North Africa, which was materialized by the French authorities, clerics and also archaeologists in Hippo.